Identification of Potential and Mitigation of Ergonomic Hazards in Stairs - Chevy Herli Sumerli A; Putri Mety Zalynda; Toto Ramadhan; Retno Aviva Ersyam; Miselia Nida Shabira (Jurnal Penelitian Pendidikan IPA, 2023)
Every job, even activity, has the potential for danger. Therefore, it is necessary to control hazards by looking for potential hazards that exist in work, work tools, workplaces and work environments, in order to reduce the risk of hazards occurring. Therefore, the aim of this research is to identify other Ergonomic Hazards to balance Job Demands and Worker Abilities. Occupational Safety and Health is not only carried out preventively by using Personal Protective Equipment but can be anticipated early by paying attention to design errors so that repairs, redesign or special handling are needed in an effort to reduce or even eliminate risks. This research will produce an Ergonomic Hazard List and mitigate the risk of danger to workers who are carrying out their work or people who are carrying out activities in a certain place. Not only when working, when doing activities you also need to pay attention to ergonomic dangers. Activities in public areas, including confined areas such as schools or campuses, must also pay attention to the potential ergonomic dangers involved. Of the many places to do activities, one of them is the stairs which have been identified as having the potential to be dangerous and pose a risk of injury. Therefore, a List of Potential Ergonomic Hazards on Stairs was designed.